D-optimal plans in observational studies - Constanze Pumplün; Stefan Rüping; Katharina Morik; Claus Weihs (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2005)
This paper investigates the use of Design of Experiments in observational studies in order to select informative observations and features for classification. D-optimal plans are searched for in existing data and based on these plans the variables most relevant for classification are determined. The adapted models are then compared with respect to their predictive accuracy on an independent test sample. Eight different data sets are investigated by this method.
Keywords: 519; D-optimality; Genetic Algorithm; Prototypes; Feature Selection